Examination of the merits and pitfalls of the internship portfolio - Kuter, Sıtkıye (Elsevier, 2009)
This study discusses the findings of a case study examining the effectiveness of the ELT internship portfolio with regard to the dimensions of its overall direction and contents, assessment procedures, and interns’ growth. The study employed a combination of quantitative and qualitative data collection and analysis procedures to investigate the issue from the standpoints of trainees, supervisors, and mentors. The analysis of multiple data yielded invaluable findings regarding the constructs of the internship portfolio displaying effectiveness and requiring further investigation and revision.
The file in this item is the publisher version (published version) of the article.
Keywords: Initial Teacher Education; Teacher Assessment; Portfolio; Developmental Assessment Tool; Teacher Development; Reflection